Maintaining Family Harmony in Islamic Law According to Madhhab of Imam Shafi’i - Mujtaba, Wardah; Saiban, Kasuwi; Rostami , Soheila (NALAR FIQH: Jurnal Hukum Islam, 2023)
ÂThis research explores and discusses the importance of maintaining family harmony in Islamic family law according to the Madhhab of Imam Syafi'i. This article, explained that maintaining family harmony is started from the attachment between husband and wife in the marriage context. Both parties must respect, appreciate, and support each other and understanding self rights and obligations. Furthermore, this article also explained the importance of good communication between family members. Each family member have to own the ability of listening and sparing time to talk to each other, then problems arises can be resolved properly. In addition, good parenting from parents to their children is also very important in maintaining family harmony. This article also emphasized the importance of avoiding actions of damaging family harmony such as infidelity, harsh words, and household violence. This could endanger family harmony and potentially caused a rift in husband and wife relationship also between parents and children. This article also emphasized the importance of maintaining the unity and entity in family, thus each family member could feel the ownership of being part of a family that supports and holds each other in life. In conclusion, this article affirmed that harmony in the family is very important in Islamic family law according to the Madhhab of Imam Shafi'i. In maintaining family harmony, each family member need to support each other and maintain the integrity of the family as a whole unit. Therefore, promoting family harmony should always be a major concern for every Muslim family.